Carbides transformations in obtaining a chromium carbide steel of the eutectic type - Shevchenko, О. М.; Maksimova, G. A.; Danilenko, N. I.; Kovylyaev, V. V.; Firstov, S. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
By the methods of raster and electron microscopy, the studies of the chromium carbide steel structure and the carbides composition are undertaken. The presence of two types of carbides is identified: a large oval rather explicit cut and thin eutectoid plates that form colonies. The stages of the carbides synthesis and their transformations during the hot deformation and the annealing are specified more precisely. The areas of the structure with high content of chromium consist mainly of (Cr, Fe)7C3 and an insignificant residual of Cr3C2; small carbides, which are in the areas with large amounts of iron, undergo a further transformation in lower chromium carbide (Cr, Fe)23C6.